Examining culturally diverse learners’ motivation and engagement processes as situated in the context of a complex task - Anyichie, Aloysius C.; Butler, Deborah L. (Frontiers in Education, 2023)
Student learning processes, including motivation and engagement, have been identified as malleable and situated in context. We have limited understanding about how to enhance motivation and engagement processes for culturally diverse learners in today’s multicultural classrooms. To support thinking about that challenge, this work built on research on both culturally responsive teaching (CRT) and self-regulated learning (SRL), each of which identifies pedagogical practices that enhance student engagement and motivation. This study examined how students at a culturally diverse public elementary school in the West Coast of Canada participated in classroom context that integrated CRT and SRL-promoting practices. Specifically, this study examined culturally diverse learners’ engagement and motivation during a complex learning task. Data collected included classroom observations, practice records and documents, students’ work samples, and student interviews and student surveys. The results demonstrated: (1) above medium levels of engagement and motivation, among participants, that varied across specific contexts; and (2) associations between culturally diverse learners’ engagement and motivation; and complex learning context such as CRT and SRL-promoting practices. Implications for future research on culturally diverse students’ engagement as well as designing a complex task that integrated a culturally responsive teaching and self-regulated learning pedagogical practices to support engagement and motivation are discussed.